Pengaruh Kualitas Informasi, Kemampuan Individual, Dan Norma Subyektif Terhadap Minat Mahasiswa Dalam Menggunakan Internet Sebagai Sumber Pustaka Dalam Penyelesaian Tugas-Tugas Kuliah (Survey Di Universitas Muhamadiyah Surakarta) - Lestari, Sri; , Drs. Yuli Tri Cahyono , M.M., Akt., CA (2015)
This research aims to analyze the influence of the quality of information, the ability of the individual and subjective norms on student interest in using the Internet as a source of literature in the completion of assignments. The data used were taken from 100 questionnaires were distributed to students S1 Faculty of Economics and Business, University of Muhammadiyah Surakarta with convenience sampling method. Data analysis techniques: (1) test data analysis, include: validity and reliability, (2) the classical assumption, consisting of: a test of normality, multicollinearity and heteroscedasticity, (3) test the hypothesis, consisting of: test multiple linear regression analysis, t test, F test and R2. The results of this study are: 1) the quality of information significantly influence the student's interest in using the Internet. 2) the ability to individually significant effect on student interest in using the Internet. 3) subjective norms significantly influence student interest in using the Internet.